Development of Real-Time Quantitative Polymerase Chain Reaction Assays to Track Treatment Response in Retinoid Resistant Acute Promyelocytic Leukemia - Jovanovic, Jelena V.; Rennie, Kristian; Culligan, Dominic; Peniket, Andrew; Lennard, Anne; Harrison, Justin; Vyas, Paresh; Grimwade, David (Frontiers in Oncology, 2011)
Molecular detection of minimal residual disease (MRD) has become established to assess remission status and guide therapy in patients with ProMyelocytic Leukemia–RARA+ acute promyelocytic leukemia (APL). However, there are few data on tracking disease response in patients with rarer retinoid resistant subtypes of APL, characterized by PLZF–RARA and STAT5b–RARA. Despite their rarity (<1% of APL) we identified 6 cases (PLZF–RARA, n = 5; STAT5b–RARA, n = 1), established the respective breakpoint junction regions and designed reverse transcription-quantitative real-time polymerase chain reaction (RT-qPCR) assays to detect leukemic transcripts. The relative level of fusion gene expression in diagnostic samples was comparable to that observed in t(15;17) – associated APL, affording assay sensitivities of ∼1 in 104−105. Serial samples were available from two PLZF–RARA APL patients. One showed persistent polymerase chain reaction positivity, predicting subsequent relapse, and remains in CR2, ∼11 years post-autograft. The other, achieved molecular remission (CRm) with combination chemotherapy, remaining in CR1 at 6 years. The STAT5b–RARA patient failed to achieve CRm following frontline combination chemotherapy and ultimately proceeded to allogeneic transplant on the basis of a steadily rising fusion transcript level. These data highlight the potential of RT-qPCR detection of MRD to facilitate development of more individualized approaches to the management of rarer molecularly defined subsets of acute leukemia.